Aplicación de un modelo de gestión estratégica y su incidencia en el mejoramiento de la administración tributaria en la región la libertad - Castillo Aguilar, Johnly Weisen (2010)
The purpose of the present investigation is to apply a Model of strategic administration for the improvement of the Tax Administration in the Region La Libertad and it is guided to propose an administration model that consists on an important methodological tool that translates the strategy in a group of performance measures, which provide the necessary structure for a better implementation of the tributary strategy and an administration system and mensuration that he/she points to obtain bigger achievements with effectiveness and efficiency, offering many advantages for its application in the Tributary Administration. The investigation problem was: The application of a Model of Strategic Administration allows the improvement of the Tributary Administration in the Region La Libertad in what measure. The hypothesis that was formulated was the following one: The application of a model of strategic administration allows the improvement of the Tributary Administration in the Region La Libertad. In the study material he/she has taken as sample to 123 employees of the Tributary Administration of the Region La Libertad, the same ones that have been selected by means of sampling probalistico using the questionnaire technique and it interviews. The used method is the descriptive one; having as results that 95% of the interviewees knows the balanced scorecard; being of application the pattern of a model of strategic administration based on the square of Integral Control of Kaplan and Norton to improve the administration of Tax Administration of the Region La Libertad finding the effectiveness, efficiency, effectiveness and the whole personnel's productivity, improving the work processes as well as promoting the voluntary execution of the taxpayers and controlling the execution of the tributary obligations in an efficient way.